The Epidemiology of Surgical Site Infections at a Tertiary Referral Hospital in a Low/Middle Income Country - Caren Challita; Nada Zahreddine; Tamara Abdallah; Nesrine Rizk; Abdul Ghani Abou Koura; Ali Slim; Nisirine Haddad; Souha Kanj; Jamal Hoballah (Journal of Global Antimicrobial Resistance)
BACKGROUND: Surgical site infections (SSIs), a common cause of healthcare-associated infections, significantly contribute to mortality and morbidity. Epidemiological data of SSIs in the Middle East and North Africa is scarce. AIM: We aimed to examine the epidemiology, clinical features, and mortality of SSIs at a Lebanese tertiary referral hospital. METHODS: A retrospective analysis of patient charts from 2019 to 2022 was conducted, identifying SSI cases based on Centers for Disease Control and Prevention/National Healthcare Safety Network definitions. Data included patient demographics, comorbidities, previous hospitalizations, risk factors, types of infections, and causative microorganisms, including multi-drug resistant organisms (MDROs). In 2021, the hospital introduced an SSI prevention bundle, incorporating updated surgical prophylaxis tailored to local epidemiology. RESULTS: The study identified 360 SSI cases. Patients had a median age of 54 years, 58% being female. Common comorbidities included hypertension (36%) and diabetes mellitus (23%). 41% had a history of malignancy. 42% were hospitalized within the last 12 months. Most surgeries were elective (81%), with a median post-operative stay of 4 days and a total hospital stay of 5 days. SSIs were classified as superficial (39%), deep/tissue (42%), or organ space (19%). In-hospital mortality rates at 30, 60, and 90 days were 1%, 2%, and 3%, respectively. Staphylococcus spp. was mostly isolated (24%), followed by Enterococcus spp. and Escherichia coli (13% each). The proportion of SSIs caused by MDROs decreased from 18% in 2019 to 4% in 2022. CONCLUSION: These findings highlight the effectiveness of epidemiologically tailored prevention strategies in reducing MDRO-related SSIs.